SPLITTING AUTOMORPHISMS OF FREE BURNSIDE GROUPS - Atabekyan, V.S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
We have proved, that if $n≥1003$ is an arbitrary odd number and $φ$ is a splitting automorphism of period $n$ of group $B(m,n)$ that has a prime order, then $φ$ is inner automorphism.
Keywords: splitting automorphism; free Burside group; holomorph of the group